Does the Hooded Crow (Corvus cornix) harbour vancomycin-resistant enterococci in Hungary? - Benmazouz, Isma; Kövér, László; Kardos, Gábor (Acta Agraria Debreceniensis, 2022)
Vancomycin resistant enterococci (VRE) are high priority nosocomial bacteria with a potential for zoonotic transmission. Thus, its emergence outside health establishments is a major concern. In order to study the prevalence of VRE in wildlife, we collected 221 faecal samples from free-ranging Hooded Crow (Corvus cornix) from urban and rural habitats in Hungary, from March to August 2020. The screening for resistant enterococci was done using bile esculin azide (BEA) agar supplemented with Vancomycin, specific to the screening of VRE. None of the samples from either habitat types yielded VRE. It seems that Hooded Crows from Hungary do not necessarily constitute a reservoir of VREs at present. Nonetheless, a continuous surveillance of VRE in wildlife would be judicious.